Kipu – Lightweight threads for Java - Dorin, Michael (2014)
This paper describes a cooperative thread scheduling mechanism, which can be used effectively on real-time java virtual machines. This scheduler is implemented using a heap-based priority queue which allows for O(log N) processing time. Since this scheduler is strictly cooperative, thread coordination is performed without the requirement of formal java thread synchronization. Though similar outcomes can be achieved through program design, this abstraction allows developers to focus on their application.